HEART UK consensus statement on Lipoprotein(a): A call to action. (December 2019) - Cegla, Jaimini; Neely, R.Dermot G.; France, Michael; Ferns, Gordon; Byrne, Chris D.; Halcox, Julian; Datta, Dev; Capps, Nigel; Shoulders, Carol; Qureshi, Nadeem; Rees, Alan; Main, Linda; et al.
Abstract: Lipoprotein(a), Lp(a), is a modified atherogenic low-density lipoprotein particle that contains apolipoprotein(a). Its levels are highly heritable and variable in the population. This consensus statement by HEART UK is based on the evidence that Lp(a) is an independent cardiovascular disease (CVD) risk factor, provides recommendations for its measurement in clinical practice and reviews current and emerging therapeutic strategies to reduce CVD risk. Ten statements summarise the most salient points for practitioners and patients with high Lp(a). HEART UK recommends that Lp(a) is measured in adults as follows: 1) those with a personal or family history of premature atherosclerotic CVD; 2) those with first-degree relatives who have Lp(a) levels >200 nmol/l; 3) patients with familial hypercholesterolemia; 4) patients with calcific aortic valve stenosis and 5) those with borderline (but <15%) 10-year risk of a cardiovascular event. The management of patients with raised Lp(a) levels should include: 1) reducing overall atherosclerotic risk; 2) controlling dyslipidemia with a desirable non-HDL-cholesterol level of <100 mg/dl (2.5 mmol/l) and 3) consideration of lipoprotein apheresis. Graphical abstract: Image 1 Highlights: The cardiovascular risk conferred by lipoprotein(a) is determined by the lipoprotein(a) serum concentration. Serum lipoprotein(a) levels should be measured in five specific population groups. Recommendations on the management of patients with raised lipoprotein(a) levels (>90 nmol/l) are discussed.